Korelasi Frekuensi Pull-Up Dengan Prestasi Tolak Peluru - Musran Musran; Yulinar Yulinar (Jurnal Dedikasi Pendidikan, 2019)
Athletics is a sports branch that in achieving its achievements influenced by components of one's physical condition is strength, arm strength grea